Increased fracture risk in prostate cancer: causes and consequences. Issue 3 (16th May 2022) - Anderson, Gordon; O'Sullivan, Joe
Abstract : Prostate cancer is associated with an increased risk of bone‐related complications, which is made worse by some of the drugs used to manage the cancer. The resulting fractures and spinal cord compression have a significant impact on patients' physical, functional and emotional wellbeing, so risks need to be assessed and managed.